Burrowing Owl (Athene cunicularia) nest phenology influenced by drought on nonbreeding grounds. (11th March 2020) - Porro, Catie M; Desmond, Martha J; Savidge, Julie A; Abadi, Fitsum; Cruz-McDonnell, Kirsten K; Davis, Jennifer L; Griebel, Randall L; Ekstein, Rebecca T; Rodríguez, Nancy Hernandez
Abstract: Migratory birds are demonstrating changes in phenology linked to climate change. Understanding these changes requires connecting events that occur over the multiple regions occupied during their annual cycle. The Burrowing Owl ( Athene cunicularia ) is a species of concern in North America, with pronounced declines in regions of the Great Plains. Using a dataset that spanned 10 breeding sites from South Dakota to northern Mexico in various years during 1989–2017, we observed both advances and delays in nesting along with increasing variation in nest initiation dates. We examined the effects of a large-scale climate system (El Niño Southern Oscillation), drought, and local weather patterns throughout the annual cycle as potential predictors of early and late nesting. Moisture conditions during the winter and spring migratory period had the greatest influence on nest phenology. Years with more intense drought on winter and migratory grounds increased the probability of nests initiating late relative to early. Correspondingly, wet conditions were associated with an increased probability of early nest initiation. Drought likely has cascading ecological effects that negatively influence food abundance for Burrowing Owls, resulting in delays in the ability of individuals to meet energetic demands required for migration. How climate change will impact Burrowing Owl phenology is important considering a projected increase in the magnitude and frequency of drought and declining owl population trends.